Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863k